Influence of storage durations on seed germination and the accumulation of chromosomal aberrations in two rice varieties (Oryza sativa L.) - Viet, Nguyen Xuan; Bich Huyen, Vu Thi (Academia Journal of Biology, 2015)
Influence of different seed storage duration on germinability and the accumulation of chromosomal aberrations was investigated in two rice varieties, 7079-Lang Son and 4134-Hoa Binh (Oryza sativa L.), long-term preserved in National seed bank. Our results showed that the germination percentages as well as mitotic index of the seeds of 7079-Lang Son stored for 9 years and of the 4134-Hoa Binh stored for 13 years have decreased slightly compared with unstored seeds. However, the seeds are stored for longer showed a significant (p<0.05) decrease in germination percentage and mitotic index, and increase in cells with chromosomal aberrations. Specially, the germination percentage dropped below 50%, mitotic index fell 27% and the frequency of abnormal cells increased very highly in 7079-Lang Son seeds stored longer than 3 years (seeds stored 12 year) as compared with near 100% (99.33%) germination as recorded for unstored seeds, suggest that the preserved seed viability may disappear completely. The relevance to these findings for the long-term conservation of rice germplasm is discussed.